High performance thin layer chromatography analysis of seed extracts of Tudri Surkh (Cheiranthus cheiri) - Erum, Aasiy Ul; Yousuf, Amjad Waheed; Aslam, M. (International Journal of Research in Medical Sciences, 2023)
Background: To develop the high-performance thin layer chromatography (HPTLC) finger print profile of hydroalcoholic and ethylalcohol extracts of seeds of Tudri Surkh (Cheiranthus cheiri). Methods: Chromatographic technique was used for separation of components from hydroalcoholic and ethylalcohol extracts of seeds and HPTLC was carried out using CAMAG HPTLC system equipped with Linomat V applicator, and WinCATS software. Results: HPTLC profiling of the extract confirm the presence of various phytochemicals. At 640 nm HPTLC finger print of hydroalcoholic extract revealed 16 components with Rf=0.05-0.94 while ethylalcohol extracts revealed 19 components peaks with Rf=0.07 to 0.96. Well separated and compact greenish, yellow and pink bands were visualized using anisaldehyde sulphuric acid reagent. Conclusions: We conclude that HPTLC fingerprint profiling of seed extracts of Tudri Surkh (Cheiranthus cheiri) revels presence of various compounds and can be utilized as a marker for standardization and proper identification of the plant material to be used for preparation of traditional drugs.